P159 Weaning And Long Term Ventilation Outcomes In Spinal Injury Patients After Referral To A Regional Spinal Injury Centre. (10th November 2014) - Pocock, AC; Nasher, M; Ward, T; Bongers, T
Abstract : Introduction: Difficult and slow weaning of ventilated patient will have been observed by staff in many critical care units 1 . A National Association for Medical Direction of Respiratory Care (NAMDRC) Consensus Conference suggested that 20% of such patients had neurological disease 2 . The incidence of respiratory failure following acute cervical spinal cord injury (ASCI) ranges between 22.6% and 57% and the average time to wean from ventilator support was found to be 36 days. Weaning for such patients should therefore take place in an intermediate care facility and be slow paced 2 . Previous data from our unit did suggest a successful wean in about 70% of patients admitted to this regional spinal injury unit 1 . We therefore wanted to review our recent results (Nov 2009 – Nov 2012) with previous standards. Methods: We performed a retrospective review of all patients admitted from November 2009 to November 2012 for respiratory weans following spinal cord insult. Results: 43 patients (35 male and 8 female) were admitted to the spinal critical care unit for weaning (14.33 patients per year). Average age was 54.7 years for male and 55.4 years for females. The level of injury is illustrated in the table below: Of the 43 patients, 35 were successfully weaned; the rest were either partially weaned or not weaned. 7 of the 10 Level C1–3 injury patients were not weaned or were only partially weaned. The remaining 3 patients of Level C1–3 injury (incomplete) were weaned. 1 patient with Level C6 injury was only partially weaned but was 77 years of age. Conclusions: Review of the period from 2009–2012 is very encouraging, suggesting weaning success in line with national and international centres. Further reviews will focus on duration of wean and the effect of co-morbidities and age on the weaning outcome. Further attention needs to focus on quality of life in the weaned and not weaned patient group. References: Watt J et al . Brit J Intensive Care AUTUMN/ 2008;95–102 MacIntyre NR et al . Chest 2005;128:3937–3954